Effect of Peanut (Arachis hypogaea) on Kidney in Rats (Delta Medical College Journal, 2014)
Background: Kidney is the main excretory organ which can be damaged by various disease conditions, foods, exposure to some chemicals, toxins, or infectious agents. Peanuts (Arachis hypogaea) may have antioxidant activity thereby can be used for the improvement of kidney functions though its exact role is yet to be explored. Objective: To observe the effect of peanut kernel powder on kidney by observing the histology and some biochemical parameters (serum creatinine and blood urea) in Wistar albino rats. Materials and method: This experimental study was conducted between October 2012 to December 2012 in the Institute of Food and Nutrition, University of Dhaka, Bangladesh. A total number of 20 apparently healthy Wistar albino male rats, weighing between 120 to 150 grams, age range 90 to 120 days were used. Prior to conducting the study, the animals were acclimatized for 14 days. Then, they were divided into two groups; control group (Group A) consisted of 10 rats and experimental group (Group B- Peanut treated group) consisted of 10 rats. All groups of animals received basal diet for 21 consecutive days and in addition, experimental group received peanut kernel powder (500mg/kg body weight/day; orally) in the morning along with food for 21 consecutive days. All the animals were sacrificed on 22nd day. The blood and kidney samples were collected. Blood urea, serum creatinine levels were measured and histopathology of kidney was done by using standard laboratory procedure. Results: The mean body weight of peanut treated group was significantly lower than that of control group. The mean blood urea and creatinine levels were higher in peanut treated group in comparison to those of control group but the differences were not statistically significant. On histology, kidney revealed normal findings both in control and peanut treated group. Conclusion: Role of peanut kernel powder in normalizing the biochemical parameters is controversial. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17792 Delta Med Col J. Jan 2014; 2(1): 17-21